Mpox Preparedness and Response 2024: Position Statement of The Disaster Management Experts Club - Heetaf Aloqaily; Rania Abdurhman Alnafea; Shahad Abdullah Alotaibi; Mohamad Bakir; Sharafaldeen Bin Nafisah; Bandr Mzahim (The Journal of Medicine, Law & Public Health)
Statement of intent